2008
DOI: 10.1111/j.1399-0039.2008.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors and CD14 genes polymorphisms and susceptibility to asthma in Tunisian children

Abstract: Many studies have shown the implication of CD14 and toll-like receptors (TLRs) 2, 4 and 9 in the pathogenesis of asthma or atopy. To evaluate the association of CD14 and TLRs gene polymorphisms with asthma or atopy, 210 asthmatic children, 224 controls and 80 families were enrolled in this study. Six single nucleotide polymorphisms TLR2 (+2408 G-->A), TLR4 (+1196 C-->T), TLR4 (+896 A-->G), TLR9 (-1237 T-->C), TLR9 (-1486 T-->C) and CD14 (-159 C-->T) were genotyped using polymerase chain reaction followed by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 38 publications
(40 reference statements)
3
60
0
4
Order By: Relevance
“…However, a number of subsequent studies yielded conflicting results regarding the association between CD14 rs2569190 and total serum IgE levels in different populations. Some studies found that the T allele was associated with a reduced risk of atopy and/or lower IgE levels (Koppelman et al, 2001;Bucková et al, 2003), while other studies found no such association (Leung et al, 2003;Eder et al, 2005), or an increased risk of atopy and higher IgE levels in subjects with the rs2569190 T allele (Jackola et al, 2006;Lachheb et al, 2008). In the present study, we found that the serum total IgE levels of TT genotype carriers were significantly higher than those in CC genotype carriers in atopic asthma patients.…”
Section: Discussionsupporting
confidence: 64%
“…However, a number of subsequent studies yielded conflicting results regarding the association between CD14 rs2569190 and total serum IgE levels in different populations. Some studies found that the T allele was associated with a reduced risk of atopy and/or lower IgE levels (Koppelman et al, 2001;Bucková et al, 2003), while other studies found no such association (Leung et al, 2003;Eder et al, 2005), or an increased risk of atopy and higher IgE levels in subjects with the rs2569190 T allele (Jackola et al, 2006;Lachheb et al, 2008). In the present study, we found that the serum total IgE levels of TT genotype carriers were significantly higher than those in CC genotype carriers in atopic asthma patients.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, TLR9 ligation on non-T cell populations has recently been shown to impair conversion of naive T cells into FoxP3 + Tregs in the periphery (54). We have also become aware of studies demonstrating associations of polymorphisms in the TLR9 gene with asthma (55,56) and Crohn disease (57). Both conditions are influenced by vitamin D deficiency (42), and it would be of interest to determine whether control of Treg function by TLR9 is implicated in these associations.…”
Section: Figurementioning
confidence: 99%
“…A study of young farmers in Germany also saw no association of TLR4 polymorphisms with asthma, allergy and atopy, however, they did observe that enhanced exposure to endotoxin in carriers of TLR4 polymorphisms had a lower incidence of asthma [15] . A study of a Tunisian population observed an association between a TLR9 polymorphism and disease susceptibility, but a study of Japanese population observed no association with this polymorphism [16,17] . In the same study of Tunisian people, prevalence of a CD14 variant was significantly higher in the asthmatic group compared to healthy controls [16] .…”
Section: Asthmamentioning
confidence: 99%
“…A study of a Tunisian population observed an association between a TLR9 polymorphism and disease susceptibility, but a study of Japanese population observed no association with this polymorphism [16,17] . In the same study of Tunisian people, prevalence of a CD14 variant was significantly higher in the asthmatic group compared to healthy controls [16] . In the past few years, several genetic loci have been implicated in development of asthma, among these, region 12q13-24 has been implicated in asthma aetiology in multiple populations [18] .…”
Section: Asthmamentioning
confidence: 99%